O papel docente do preceptor no Programa de Residência Multiprofissional em Saúde da Universidade Federal do Amazonas - Souza, Sanay Vitorino de (2016)
This study had as objective to analyse the teaching role of the professionals involved with the mentoring activity in the Multidisciplinary Residency Program in Health of the Federal University of Amazonas. It’s a qualitative research, with descriptive and exploratory character. The study was accomplished in a university hospital in the city of Manaus - AM. The data were collected by means of documental analysis, half-structured interview and application of attitudinal instrument Likert type. The population was composed for preceptors and residents. The data collection was divided in two stages. In the first stage, interview with 10 preceptors of the program was accomplished. The interviews were recorded, transcribing and the data analysed by means of the technique of content analysis, thematic modality. By means of the analysis of the interviews, it was possible to know to the light of the preceptors, the meaning of an ideal preceptorship. Four axles drivers had organized the process of the content analysis: the relevance of the preceptorship for the process of training in health; the preceptorship as pedagogical activity and the ideal preceptor; the permanent education in health – EPS and the improvement of the preceptorship; the preceptorship and the theoretical joint/practice. The perceptions harvested by means of the instrument of the Likert type next to these preceptors increased of the participation of the residents in its first and according to year had pointed with respect to a assertiveness in the drawing of the Program. The study is in consonance with the ethical principles of research and had an authorization granted by the Ethics Committee on Research of the Federal University of São Paulo, by CAAE: 43331215.0.0000.5505. Therefore, it is believed that the study has brought new and relevant information considered and highlighted by preceptors and residents: adequate theoretical construction and practice developed as a qualifying element for the training process from the needs presented by the residents; the encouragement of a critical and reflective attitude about the care provided by them; the defense of the determinants of health and the biological and social determinants of disease; encouraging the development of networking an integral perspective of care, and the option for multiprofessional and collaborative work as a way to interprofissionalidade in line with the recommendations in the Pedagogical Political Project of the Multidisciplinary Residency in Health and the Coordination of Multidisciplinary Residency.